Demographic and diagnostic characteristics of the first 1000 patients enrolled in the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD). - Kogan, J; Otto, M; Bauer, MS; Dennehy, E; Miklowitz, D; Zhang, H; Ketter, T; Rudorfer, M; Wisniewski, SR; Thase, M; Calabrese, J; Sachs, G (2004)
OBJECTIVES: Bipolar disorder is a severe, recurrent, and often highly impairing psychiatric disorder. The Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) is a large-scale multicenter study funded by the National Institute of Mental Health (NIMH) to examine the longitudinal course of the disorder and the effectiveness of current treatments. The current report provides a context for interpreting studies resulting from STEP-BD by summarizing the baseline demographic and diagnostic characteristics of the first 1000 enrolled. METHODS: The majority of the sample met DSM-IV criteria for bipolar I disorder (71%). Mean age of patients was 40.6 (+/-12.7) years and mean duration of bipolar illness was 23.1 (+/-12.9) years. Among the first 1000 subjects enrolled, 58.6% are females and 92.6% Caucasian. This report compares the STEP-BD sample with other large cohorts of bipolar patients (treatment and community samples). RESULTS: Compared with US population and community studies, the first 1000 STEP-BD patients were less racially diverse, more educated, had lower income, and a higher unemployment rate. Results are discussed in terms of the contributions of STEP-BD (and other large-scale treatment studies) in understanding the nature, treatments, and outcomes of bipolar disorder for patients seeking care at academic treatment centers. CONCLUSIONS: The current report provides a context for interpreting future studies resulting from STEP-BD. The comparison of demographic and clinical characteristics between the samples across clinic-based studies suggests broad similarities despite the substantial differences in geography, payer mix, and clinical entry point.